The Ile191Val Variant of the TAS1R2 Subunit of Sweet Taste Receptors Is Associated With Reduced HbA1c in a Human Cohort With Variable Levels of Glucose Homeostasis - Serrano, Joan; Yi, Fanchao; Smith, Joshua; Pratley, Richard E.; Kyriazis, George A. (Frontiers in Nutrition, 2022)
The Ile191Val variant of the TAS1R2 gene of sweet taste receptors causes a partial loss-of-function and is associated with reduced glucose excursions in a healthy lean cohort. However, it is unclear whether this polymorphism contributes to the regulation of glucose homeostasis in metabolically unhealthy individuals. Thus, we used participants with variable glycemic profiles and obesity to assess the effects of the TAS1R2-Ile191Val variant. We found that the Val minor allele carriers had lower HbA1c at all levels of fasting glucose and glucose tolerance. These effects were not due to differences in beta-cell function or insulin sensitivity assessed with a frequently sampled intravenous glucose tolerance test. This study extends our previous findings and provides further evidence that sweet taste receptor function may contribute to glucose regulation in humans.